Analysis of Work Position on Subjective Complaints Musculoskeletal Disorders Construction Welding Workers PT. Swabina Gatra - Inayah, Zufra; Anggraeni, Arvina Diah; Jihad, Muhammad; Syahputra, Rizki Aryadinata (Universitas Ibn Khaldun Bogor, 2025)
Background: Work position is a posture that is formed naturally by the body related to work habits and facilities used in a job. Work positions that are not ergonomic cause several complaints to the body, one of which is the occurrence of MSDs, which is a discomfort in the muscles and bones of a person's skeleton starting from very mild to very severe pain complaints. Purpose: of this research is to describe and analyze the work position on the occurrence of complaints of Musculoskeletal Disorders in welding workers in the workshop area of PT. Swabina Gatra Tuban. Method: This research is a descriptive observational study with 4 welding workers as respondents. The variables studied were complaints of MSDs and the level of risk of work posture. The method used to identify the level of risk in the work position is the Rapid Entire Body Assessment method and the identification of MSDs complaints using the Nordic Body Map. The data analysis used cross tabulation. Result: of this study indicate that the risk level of a low work position to a low level of subjective complaints gets a percentage (25%), and a moderate level of risk to a moderate level of subjective complaints gets a percentage (75%). Conclusion: of this study is that there are complaints of MSDs and the work position of welders who have risks. It is recommended for companies to provide counseling related to work positions, stretching programs and procurement of ergonomic work aids.